Scientific Bibliography in the State Public Scientific Technological Library of the Siberian Branch of the Russian Academy of Sciences: Stages of Development, Modern Realities and Prospects - T. V. Busygina; L. A. Mandrinina; V. V. Rykova; N. A. Balutkina (Библиосфера)
The article objective is to show the bibliographic activity development on information research support in the State Public Scientific Technological Library of the Siberian Branch of the Russian Academy of Sciences (SPSTL SB RAS). Namely, changes in the technology of creating information resources of own generation due to computers and software; to represent the product types created by employees during 1958–2021; to highlight topics of traditional bibliographic current and retrospective indexes, bibliographic and full-text databases. The paper presents quantitative characteristics of the generated electronic resources; shows the forms of bibliographic services: information selective dissemination, differentiated services for managers, electronic thematic exhibitions of literature based on the databases; gives a brief description of bibliometric research. The authors determine prospects to develop the number of SPSTL SB RAS information and bibliographic complex. They are growing the authoritative data files in bibliographic databases, expanding the repertoire of Open Access sources to select information for regional bibliographic resources, developing interactive forms of information services for scientists and specialists; participating the semantic web through linked data technology based on authoritative files as an object (predicate), improving the service capabilities of the information search system (access to full texts).